Physical Performance of Cucumis melo var. inodorus Fruit under Different Storage Conditions - Nurul Habibah; Nasrudin Nasrudin; R. Arif Malik Ramadhan (JURNAL TRITON, 2026)
Melon is an economically important horticultural crop, widely cultivated for its sweet taste and nutritional benefits. However, its postharvest quality is strongly affected by storage conditions, particularly temperature, which can alter the fruit’s physiology, weight, texture, and shelf life. This study aims to evaluate the effect of storage temperature on the physical quality and shelf life of Cucumis melo var. inodorus. The study used a Completely Randomized Design with storage temperature treatments, namely, room temperature and low temperature, with five replications. Observed variables included fruit length, fruit diameter, fruit weight, skin and flesh thickness, flesh color, texture, and shelf life during the storage period. The results showed that storage at low temperature was able to maintain weight, skin and flesh thickness, firmness, and delayed color changes, while room temperature accelerated water loss, tissue softening, and color changes. Correlation analysis revealed that greater fruit diameter was positively correlated with both fruit weight and shelf life, whereas high temperature had a negative influence on these traits. Overall, storing melon at low temperatures extended its shelf life by approximately eight days compared to room temperature, while also preserving the fruit’s physical quality. These findings provide practical guidance for farmers, distributors, and retailers to minimize losses, maintain consumer quality, and enhance the market competitiveness of Cucumis melo var. inodorus.